Solved – Calculating joint density function of Brownian motion

brownian motionmarkov-processprobability

I read in my book today regarding the calculation of the joint density function of a brownian motion process and it went as follows:

If we define $X(t)$ as a Brownian motion process with mean $0$ and variance $t$, to obtain the joint density function of $X(t_1), … , X(t_n)$ for $t_1 < \cdots < t_n$, note that the set of equalities,

$$
X(t_1) = x_1, X(t_2) = x_2, … , X(t_n) = x_n
$$

is equivalent to

$$
X(t_1) = x_1, X(t_2)-X(t_1) = x_2-x_1, … , X(t_n)-X(t_{n-1}) = x_n-x_{n-1}.
$$

then, the joint density of $X(t_1) = x_1, X(t_2) = x_2, … , X(t_n)$ is

$$
f(x_1,…,x_n) = f_{t_1}(x_1) \cdot f_{t_2 – t_1}(x_2-x_1)\cdots f_{t_n – t_{n-1}}(x_n – x_{n-1}).
$$

I am confused why we are allowed to directly input the second set of equalities into the density function. Wouldn't it yield a different result as we are indirectly calculating each $x_i$? Would anyone be able to help me? Thank you!

Best Answer

The other answer doesn't really give the full story. It's the transformation theorem. I just had an answer involving it here.

Call $$X(t_1) = Y_1,~X(t_2) = Y_2 + Y_1, ...,~X(t_n) = Y_n + \cdots + Y_1.$$ The inverse transformations are $$Y_1 = X(t_1),~Y_2 = X(t_2)-X(t_1), ..., ~Y_n = X(t_n) - X(t_{n-1}).$$ We know the joint density of all the $Y$s is the product of mean zero gaussians with variances $\sigma^2 t_1$, $\sigma^2 (t_2-t_1),\ldots, \sigma^2(t_n-t_{n-1})$. We're using the independent and stationary increments properties here. We will call this product of Gaussians $f_{Y_1,\ldots,Y_n}(y_1,\ldots,y_n) = f_{Y_1}(y_1)\cdots f_{Y_n}(y_n)$. Looking at the matrix of partial derivatives, its determinant is $1$.

So this is why you just plug stuff in. The density of $X(t_1),\ldots, X(t_n)$ is \begin{align*} g_{X(t_1),\ldots, X(t_n)}(x_1,\ldots,x_n)&=f_{Y_1,\ldots,Y_n}(y_1[x(t_1),\ldots,x(t_n)],\ldots,y_n[x(t_1),\ldots,x(t_n)])|1|\\ &= f_{Y_1,\ldots,Y_n}(x(t_1),x(t_2)-x(t_1),\ldots,x(t_n)-x(t_{n-1})) \\ &= f_{Y_1}(x(t_1))f_{Y_2}(x(t_2)-x(t_1))\cdots f_{Y_n}(x(t_n)-x(t_{n-1})). \end{align*}

Related Question